Pengaruh Kualitas Produk, Harga dan Citra Merek Terhadap Keputusan Pembelian Konsumen Handphone Merek Iphone Kota Semarang - Chardika Respatya Hendro; Wahyu Hidayat (Universitas Diponegoro, 2018)
The technological development in the modern era is rapidly growing and especially in mobile phone segment. Iphone brand is one of the choices that available in the market. The purchase decision of this the Iphone brand can be influenced by Product Quality, Price and Brand Image. The aim of this research is to determine the effect of product quality, price and brand image on the purchase decision of the Iphone brand in Semarang City. This research are using explanatory research model, nonprobability sampling technique with accidental sampling method for sampling technique, interview questionnaires for colleting data, and a total sample of 97 respondents. This research also uses quantitative analysis with validity test, reliability test, correlation coefficient, determination coefficient, simple and multiple regression test, significance of t test, and F test. The results of this research are the product quality affects the purchasing decisions by 31.3%, price affects the purchasing decisions by 26.4%, brand image affects the purchasing decisions by 30%. Simultaneously, the product quality, price and brand image affect the purchasing decision of 42.2% while the remaining 57.8% is influenced by other factors. The result of this research indicates that this three variables; product quality, price and brand image, simultaneously have a positive and significant effect on consumer purchasing decisions of the Iphone brand in Semarang City. The suggestions of this research in terms of product quality are to make the batteries that last for longer time and to use a strong material to build the mobile phone. In terms of price, the suggestion is to set a price that can be reached by many segments. The last, in terms of brand image, the suggestion is to provide a system that can provide more benefits to its users.